Mineralization of Thippi (Cassava Starch Factory Solid Residue) Compost Under Incubation - S., Chithra; K., Susan John; J., Sreekumar; M., Manikantan Nair (JOURNAL OF ROOT CROPS, 2021)
Cassava (Manihot esculenta Crantz) is an important tropical tuber crop, the tubers of which are used both for edible purpose and for industrial uses. In Tamil Nadu, more than 500 cassava based small to large scale starch and sago producing factories are generating more than 250 tonnes of solid residue called ‘thippi’ per annum. This is an environmental pollutant affecting soil and human health and was found very difficult to dispose too. At ICAR-CTCRI, the same was converted to a nutritious organic manure through different composting methods where comosting resulted in the highest nutrient increase and the C: N ratio narrowed to 8:1 from 82:1. Experiments conducted in cassava showed its suitability as a good organic manure alternative to the commonly used organic manures like farm yard manure, green manuring in situ with cowpea, vermicompost, coir pith compost and crop residue as well as can substitute for 50% of the NPK requirement as per package of practices (PoP) and secondary nutrient Mg and micronutrient Zn to a great extent. While using any organic manure, the decomposition of the same to release the nutrients (mineralization) especially during the critical growth stage of the crop or as per the nutrient requirement of the crop needs to be understood. Hence, to understand the nutrient release pattern of thippi compost, a pot study was conducted by incubating the soil mixed with thippi compost and analysed the soil samples at monthly intervals for pH, organic carbon, electrical conductivity (EC), available N, P and K, exchangeable Ca, Mg, Fe, Cu, Mn and Zn for one year. The mean data of the soil chemical properties for one year indicated the pH, EC, available N, P and K, exchangeable Ca, Mg, available S, Fe, Cu, Mn, Zn and B increased to the tune of 0.64, 0.055 dS m- 1, 99.8, 46.1, 87.2 kg ha-1, 0.73, 0.99 meq 100g-1, 15.8, 9.4, 0.18, 1.07, 3.07 and 0.19 mg kg- 1 which in turn was 13.8 , 35.4, 46, 88.3, 107.5, 68.2, 176.7, 158, 23.5, 16.4, 72.8, 56.7 and 17.9% over the initial status. Among the nine composting options, vermicomposted thippi compost had the highest nutrient release and the maximum nutrient release was found during 5 to 8th month of incubation.